Partisipasi Perguruan Tinggi Pada Kegiatan Hari Jadi Kelurahan Gombengsari Kabupaten Banyuwangi - Gatut Rubiono; Adi Mulyadi; Edvin Cahyono (Fakultas Teknik, Universitas PGRI Banyuwangi, 2023)
Community service is one of the dharma and obligations of college. One form of activity is participation in activities at the village/kelurahan level. The writing of this article aims to describe the participation of college in the anniversary activities of the Gombengsari village, Banyuwangi district. Participation is carried out according to the invitation of the organizing committee. Participation was carried out from elements of structural officials, the unit of Humas dan Penerimaan Mahasiswa Baru and university students. University have participated in enlivening and enlivening activities in the form of ceremonial events, exhibition and environmental dialogues.